1999
DOI: 10.1007/s11661-999-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pressing speed on microstructural development in equal-channel angular pressing

Abstract: The influence of pressing speed in equal-channel angular (ECA) pressing was investigated using samples of pure Al and an Al-1 pct Mg alloy and a range of pressing speeds from ϳ10 Ϫ2 to ϳ10 mm s Ϫ1 . The results show that the speed of pressing has no significant influence on the equilibrium grain size, at least over the range used in these experiments. Thus, the equilibrium grain sizes were ϳ1.2 m for pure Al and ϳ0.5 m for the Al-1 pct Mg alloy for all pressing conditions. However, it is shown that the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(71 citation statements)
references
References 22 publications
1
70
0
Order By: Relevance
“…Vickers microhardness HV0.1 (F=100 g, dwell time t=10 s) was measured on a semi-automatic Wolpert tester allowing automatic indentation. The variations of microhardness along the different surfaces of ECAP billets were inspected by making 3 lines of indents; one in the centre and other two 2.5 mm from the edge of each plane of the billet (X, Y and Z plane) [10].…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vickers microhardness HV0.1 (F=100 g, dwell time t=10 s) was measured on a semi-automatic Wolpert tester allowing automatic indentation. The variations of microhardness along the different surfaces of ECAP billets were inspected by making 3 lines of indents; one in the centre and other two 2.5 mm from the edge of each plane of the billet (X, Y and Z plane) [10].…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The most probable recovery mechanisms are the mutual annihilation of dislocations and/or their rearrangement into lower energy structures with increasing strain imposed to the material by ECAP [2,10]. Fig.…”
Section: Dislocation Densitymentioning
confidence: 99%
“…The revealed that the temperature range for ECAP in order to control the resulting microstructure as a variety of phase transformations might occur in this metastable β-Ti alloy at elevated temperatures. They found that the ECAP at 673 K led to the occurrence of omega (ω) phase in alloy and resulted in higher strength and hardness but less ductility compared with those in the alloy processed at a a higher temperature of 903 K. [20] Miroslav et al [21] investigated the effect of ECAP on the microstructure and the mechanical properties of CP-Ti and demonstrated that the main mechanism of significant strengthening of Ti increases was grain refinement. The UFG-Ti has higher specific strength than ordinary Ti.…”
Section: Effect Of Ecap On Mechanical Propertiesmentioning
confidence: 99%
“…The principles of ECAP are depicted schematically in figure 1 [13] . The sample, in the form of a rod or bar, is machined to fit within a channel contained in an ECAP die and it is then pressed through the die using a plunger.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On N T To O S Se Ev Ve mentioning
confidence: 99%
“…It can be shown from simple geometric calculations that the strain imposed on the sample in a single pass depends primarily upon the angle between the two parts of the channel but also to a minor extent upon the magnitude of the F Fi ig gu ur re e 1 1. The principles of ECAP [13] .…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On N T To O S Se Ev Ve mentioning
confidence: 99%